A highly multiplexed quantitative phosphosite assay for biology and preclinical studies. Issue 9 (27th September 2021) - Keshishian, Hasmik; McDonald, E Robert; Mundt, Filip; Melanson, Randy; Krug, Karsten; Porter, Dale A; Wallace, Luke; Forestier, Dominique; Rabasha, Bokang; Marlow, Sara E; Jane‐Valbuena, Judit; Todres, Ellen; et al.
Abstract: Reliable methods to quantify dynamic signaling changes across diverse pathways are needed to better understand the effects of disease and drug treatment in cells and tissues but are presently lacking. Here, we present SigPath, a targeted mass spectrometry (MS) assay that measures 284 phosphosites in 200 phosphoproteins of biological interest. SigPath probes a broad swath of signaling biology with high throughput and quantitative precision. We applied the assay to investigate changes in phospho‐signaling in drug‐treated cancer cell lines, breast cancer preclinical models, and human medulloblastoma tumors. In addition to validating previous findings, SigPath detected and quantified a large number of differentially regulated phosphosites newly associated with disease models and human tumors at baseline or with drug perturbation. Our results highlight the potential of SigPath to monitor phosphoproteomic signaling events and to nominate mechanistic hypotheses regarding oncogenesis, response, and resistance to therapy. SYNOPSIS: SigPath is a targeted, quantitative mass spectrometry assay that measures 284 phosphosites spanning 200 phosphoproteins with high throughput and quantitative precision across a broad swath of signaling biology of known interest. The value of the assay is demonstrated by application to drug‐treated cancer cell lines, breast cancer preclinical models and human medulloblastoma tumors. Large numbers of differentially regulated phosphosites newly associated with disease models and human tumors are identified. The results highlight the potential use of SigPath to nominate mechanistic hypotheses regarding oncogenesis, response and resistance to therapy. Abstract : SigPath is a targeted, quantitative mass spectrometry assay that measures 284 phosphosites spanning 200 phosphoproteins with high throughput and quantitative precision across a broad swath of signaling biology of known interest.